“Las administraciones, que mantienen á la Nacion estacionaria en su estado de atraso”: El apoyo de la prensa regional al tercer gobierno de Ramón Castilla como forma de resistencia a la autoridad local (1855-1860) - Gil Ichillumpa, Rubén (Pontificia Universidad Católica del Perú, 2024)
Outside of Lima, support for the central government, focused on Ramón Castilla and the constitutions of 1839 and 1856, was used as a tool to confront the abuses of power by local administrations. This was evidenced in numerous articles in the regional press, where attacks on press freedom and even personal attacks were highlighted and denounced as part of the arbitrariness of the prefects, their inefficiency, and their failure to follow the ideals of the government.

Fuera de Lima, el apoyo al gobierno central, enfocado en la figura de Ramón Castilla y las constituciones de 1839 y 1856, tenía como fin enfrentar los abusos de poder de las administraciones locales. Este hecho se evidenció en numerosos artículos de la prensa regional, en los que el ataque contra la libertad de prensa e incluso personal eran muy claros. Son extractos de artículos que también denuncian la arbitrariedad de los prefectos, su ineficacia y el hecho de que no estaban siguiendo los ideales del gobierno.
“The administrations that keep the Nation stagnant in its state of backwardness”: Regional press support for the Third Government of Ramón Castilla as resistance to local authority (1855-1860)
Keywords: Regional History of Peru; Liberalism; Ramón Castilla; Press; Prefectures; Historia regional del Perú; Liberalismo; Ramón Castilla; Prensa; Prefecturas; https://purl.org/pe-repo/ocde/ford#6.00.00